1997
DOI: 10.1021/cm9704241
|View full text |Cite
|
Sign up to set email alerts
|

Colossal Magnetoresistance in the Transition-Metal Zintl Compound Eu14MnSb11

Abstract: Magnetoresistance measurements have been carried out on single-crystal sample of the transition-metal Zintl compound Eu 14 MnSb 11 . Eu 14 MnSb 11 is the first compound of the Ca 14 -AlSb 11 structure type in which magnetoresistive effects have been measured. Colossal magnetoresistance (CMR) at 92 K and 5 T with ∆F/F(0) ) -36% and at 5 K and 5 T with ∆F/F(0) ) -42% were observed. CMR is observed at the ferromagnetic-paramagnetic phase transition (92 K). A large negative magnetoresistance is observed below the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
111
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 39 publications
3
111
1
Order By: Relevance
“…Magnetoresistance (MR) has been observed in several rare-earth Zintl analogues. 6,[8][9][10][14][15][16][17] It is thought that the MR behavior of rare-earth-containing Zintl phases originates from interactions between the localized magnetic moment on the rare-earth cations and the delocalized conduction electrons of the Zintl polyanions. Such materials could be useful in magnetic storage applications.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetoresistance (MR) has been observed in several rare-earth Zintl analogues. 6,[8][9][10][14][15][16][17] It is thought that the MR behavior of rare-earth-containing Zintl phases originates from interactions between the localized magnetic moment on the rare-earth cations and the delocalized conduction electrons of the Zintl polyanions. Such materials could be useful in magnetic storage applications.…”
Section: Introductionmentioning
confidence: 99%
“…The Zintl phase Eu 14 MnSb 11 , exhibits colossal magnetoresistance (up to À36%) and shows a ferromagnetic transition at 92 K [2]. Recently, the first Pr-based heavy-fermion compound, PrOs 4 Sb 12 , was found to be superconducting below T C ¼ 1:85 K [3].…”
Section: Introductionmentioning
confidence: 99%
“…The optical spectra originate mainly from the transitions between occupied Eu 4f states and unoccupied Eu 5d states. It is demonstrated that the two-dimensional ½GaðP=AsÞ 2 network in EuGa 2 P 2 and EuGa 2 As 2 is favorable for thermoelectric applications as compared to the three-dimensional ½GaSb 2 Zintl phases have received great interest because of their fascinating structural variety and applications. Their physical properties include complex magnetic ordering and superconductivity.…”
mentioning
confidence: 99%
“…Their physical properties include complex magnetic ordering and superconductivity. 1,2 Recently, Zintl phases have also been recognized as a new material class for thermoelectric applications. 3 Rare earth analogues of alkali or alkaline earth Zintl phases achieve the same complexity and variety as their main group counterparts but also show colossal magnetoresistance (CMR).…”
mentioning
confidence: 99%
See 1 more Smart Citation